2016
DOI: 10.1021/acs.nanolett.6b01169
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable Superhydrophobicity from Monolithic, Three-Dimensional Hierarchical Wrinkles

Abstract: We report the design of three-dimensional (3D) hierarchical wrinkle substrates that can maintain their superhydrophobicity even after being repeatedly stretched. Monolithic poly­(dimethysiloxane) with multiscale features showed wetting properties characteristic of static superhydrophobicity with water contact angles (>160°) and very low contact angle hysteresis (<5°). To examine how superhydrophobicity was maintained as the substrate was stretched, we investigated the dynamic wetting behavior of bouncing and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 36 publications
1
130
0
Order By: Relevance
“…[71] Hierarchical wrinkles are wrinkled microstructures that span multiple length scales by displaying multiple "generations" of wrinkles on one substrate, further extending the potential of these self-forming masters. [72] Such hierarchical wrinkles have been fabricated following either a wrinkles on wrinkles approach ( Figure 2B) or by decorating micropatterned elastomers with wrinkles ( Figure 2C). The general procedure for generating wrinkles on wrinkles is as follows: (i) the first 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 generation of wrinkles (G1 wrinkles) is fabricated by coating hard skins on pre-strained elastomeric surfaces using oxidation or REI treatment (as described above, Figure 2B); (ii) strain is partially released on the substrate, resulting in a state of strain below the initial pre-strain but above 0, and the substrate is subjected to a second round of oxidation or RIE (for PDMS or polystyrene, respectively) to generate a second hard surface layer; and (iii) pre-strain is released, yielding a second generation of wrinkles (G2 wrinkles) of longer wavelength that are coated with the original, short wavelength wrinkles.…”
Section: "Self-forming" Mastersmentioning
confidence: 99%
See 1 more Smart Citation
“…[71] Hierarchical wrinkles are wrinkled microstructures that span multiple length scales by displaying multiple "generations" of wrinkles on one substrate, further extending the potential of these self-forming masters. [72] Such hierarchical wrinkles have been fabricated following either a wrinkles on wrinkles approach ( Figure 2B) or by decorating micropatterned elastomers with wrinkles ( Figure 2C). The general procedure for generating wrinkles on wrinkles is as follows: (i) the first 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 generation of wrinkles (G1 wrinkles) is fabricated by coating hard skins on pre-strained elastomeric surfaces using oxidation or REI treatment (as described above, Figure 2B); (ii) strain is partially released on the substrate, resulting in a state of strain below the initial pre-strain but above 0, and the substrate is subjected to a second round of oxidation or RIE (for PDMS or polystyrene, respectively) to generate a second hard surface layer; and (iii) pre-strain is released, yielding a second generation of wrinkles (G2 wrinkles) of longer wavelength that are coated with the original, short wavelength wrinkles.…”
Section: "Self-forming" Mastersmentioning
confidence: 99%
“…Due to the presence of multiple wavelengths of wrinkles, these PMs can be used as dynamic superhydrophobic surfaces [73,89,90] that retain the ability to shed water when twisted or bent. [72] In addition to applications in superhydrophobic surfaces, PMs based on hierarchal wrinkles have applications in the creation of microcircuits [91] and the fabrication of open channel microfluidic devices. [92]…”
Section: "Self-forming" Mastersmentioning
confidence: 99%
“…The PDMS surface shows superhydrophobicity with a maximum water CA of 154.5 • ± 1.7 • and a transparency over 91%, a light loss of less than 1% compared with flat PDMS in the visible range (Figure 9f). Lee et al [103] reported a three-dimensional hierarchical wrinkled PDMS surface that can exhibit superhydrophobicity even after being repeatedly stretched. They produced these surfaces by molding against polystyrene (PS) templates designed by sequential wrinkling.…”
Section: Reactive Ion Etchingmentioning
confidence: 99%
“…Taking natural non‐wetting surfaces as inspiration artificial superhydrophobic substrates have been fabricated and used in many technical applications . When these substrates are partially immersed in water, air is trapped in between the rough surface features and an air phase‐dependent, constant and plentiful interfacial oxygen level can be maintained.…”
Section: Introductionmentioning
confidence: 99%